2009
DOI: 10.1002/j.2333-8504.2009.tb02175.x
|View full text |Cite
|
Sign up to set email alerts
|

The Toeic® Speaking and Writing Tests: Relations to Test‐taker Perceptions of Proficiency in English

Abstract: To facilitate the interpretation of test scores from the new TOEIC ® speaking and writing tests as measures of English-language proficiency, we administered a self-assessment inventory to TOEIC examinees in Japan and Korea, to gather their perceptions of their ability to perform a variety of everyday English-language tasks. TOEIC scores related relatively strongly to test taker self-reports for both speaking and writing tasks. The results were extraordinarily consistent, with examinees at each higher TOEIC sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…These statements were selected from longer selfassessment inventories that had been administered in previous studies of the TOEIC tests (Powers, Kim, & Weng, 2008;Powers, Kim, Yu, Weng, & VanWinkle, 2009). For the current effort, the sample of tasks was selected from the longer assessments so as to represent a range of activities of varying content and degree of difficulty, as estimated from the previous self-assessment studies referenced above.…”
Section: Methodsmentioning
confidence: 99%
“…These statements were selected from longer selfassessment inventories that had been administered in previous studies of the TOEIC tests (Powers, Kim, & Weng, 2008;Powers, Kim, Yu, Weng, & VanWinkle, 2009). For the current effort, the sample of tasks was selected from the longer assessments so as to represent a range of activities of varying content and degree of difficulty, as estimated from the previous self-assessment studies referenced above.…”
Section: Methodsmentioning
confidence: 99%
“…He found the following activities to feature most prominently in business contexts: writing and reading of e-mails and reports, formal, and informal meetings, telephoning, conferences, seminars, and presentations. Similar tasks were identified by Singh and Shamsudin (2009) in their analysis of written workplace communication in Malaysia as well as by Powers et al (2009) who asked 3,814 test takers who took the TOEIC ® assessment which tasks they were usually engaged in and able to do in their respective workplace settings. Moreover, Holmes (2000), who focused on oral means of communication in professional contexts in New Zealand, identified meetings, telephone conversations, and social talk as crucial workplace tasks.…”
Section: Pragmatic Competence In the Language Use Domain "Workplace"mentioning
confidence: 56%
“…Second, with regard to business-oriented communication, several studies have identified a range of tasks in business interactions (e.g., Clyne, 1994;Evans, 2013;Flowerdew & Wan, 2006;Holmes, 2000;Koester, 2010;Lan & MacGregor, 2010;Marra, 2012;Powers, Kim, Yu, Weng, & VanWinkle, 2009;Singh & Shamsudin, 2009;Wenger, 1998;Willing, 1992Willing, , 1997. Although it is impossible to provide an exhaustive description, as each workplace has its own genres and communities of practice, several studies have identified and examined tasks that range across a broad variety of professional and business contexts.…”
Section: Pragmatic Competence In the Language Use Domain "Workplace"mentioning
confidence: 99%
See 1 more Smart Citation
“…Automated scoring of speaking as discussed above, could help to reduce costs, but is not yet sufficiently well developed (Bridgeman et al 2012). The TOEIC ® Speaking and Writing test followed the TOEFL (Pearlman 2008b) in using ECD for assessment design (Hines 2010) as well as in the inclusion of speaking (Powers 2010;Powers et al 2009). …”
Section: Speakingmentioning
confidence: 99%